Aplikasi Minyak Atsiri dari Tanaman Serai Wangi sebagai Antifungi pada Fusarium oxysporum f. sp. lycopersici. Patogen Tanaman Tomat - Musafir; Anton Muhibuddin Anton Muhibuddin; Mintarto Martosudiro (Yayasan Tajuk Indonesia, 2025)
Tomato (Lycopersicon esculentum Mill.) is one of the important horticultural crops that are widely cultivated in various countries, including Indonesia. The process of cultivating and producing tomato commodities in Indonesia generally still experiences obstacles. This is influenced by various factors, one of which is an attack from pathogenic fungi in the form of Fusarium oxysporum f. sp. lycopersici. Fusarium wilt caused by the fungus Fusarium oxysporum f. sp. lycopersici. can cause severe damage to tomato plants which results in decreased yields and economic losses for farmers. The use of essential oils extracted from citronella plants as a control agent for fusarium wilt disease in tomato plants is a promising approach to controlling plant diseases biologically. This research was conducted from August 2023 to April 2024, located at the Plant Disease Laboratory and at the Kawat house, Faculty of Agriculture, Brawijaya University, Malang. The research was conducted using an experimental method and arranged using a Completely Randomized Design (CRD). The results obtained in this study were that the application of essential oils with a concentration of 333 ppm to 1000 ppm effectively (<0.005%) inhibited the growth of Fusarium oxysporum f. sp. lycopersici fungal colonies. This was indicated by a decrease in the dry weight of the fungal colonies at each increase in the concentration of essential oils, namely with a percentage of 33.13%, 41.02%, and 55.15%. Meanwhile, the application of essential oils had a significant effect (<0.005%) on the incidence of disease in tomato plants, with a percentage of disease incidence of 63%, 38%, 25%, and 13%.